The Effectiveness of Using Gym Ball in Reducing Back Pain in the Third-Trimester Pregnant Women - Wulandari, Heny; Kurniawati, Indah; Winarna, Nuristy Brillian Ainindiyahsari (Jurnal MIDPRO, 2024)
Back pain is one of the problems that pregnant women often experience during the third trimester. If the pain is not treated immediately, it will have serious consequences for the mother. One effort is simple physical therapy using a ball, which is useful for strengthening the abdominal and lower back muscles. It is usually called gymball training. This study aimed to determine how effectively a gym ball reduces back pain felt by pregnant women in the third trimester.This research used a pre-experiment with one pretest-posttest group and a sample of 30 pregnant women in the Singojuruh Public Health Center area. It was conducted from September to October 2023. This study applied simple random sampling techniques to determine the sample and analyse data using the Wilcoxon test.This study revealed that the prevalence of back pain in pregnant women was reduced from 43.3% to 6.7% for pain in the moderate category. Furthermore, 10% of respondents no longer felt back pain after using the gymball. Based on the Wilcoxon signed ranks test results on data before and after testing, a p-value of 0.000 was obtained, which shows that using a gym ball effectively treats back pain in pregnant women in the third trimester. The use of a gym ball can be used as a complementary care alternative to relieve pregnant women's back pain during pregnancy, especially in the third trimester. It is hoped that this gymball can be implemented in health facilities in classes for pregnant women.